A comparison of outcomes between Canada and the United States in patients recovering from hip fracture repair: secondary analysis of the FOCUS trial - BEAUPRE, LAUREN A.; WAI, EUGENE K.; HOOVER, DONALD R.; NOVECK, HELAINE; ROFFEY, DARREN M.; COOK, DONALD R.; MAGAZINER, JAY S.; CARSON, JEFFREY L. (International journal for quality in health care, 2018)
Abstract Objective To determine if adjusted mortality, walking ability or return home differed after hip fracture surgery between Canada and the USA. Design Secondary analysis of the Functional Outcomes in Cardiovascular Patients Undergoing Surgical Hip Fracture Repair (FOCUS) trial data. Setting Data were collected from 47 American and Canadian hospitals. Participants Overall, 2016 subjects with a hip fracture (USA = 1222 (60.6%); Canada = 794 (39.4%)) were randomized to a liberal or restrictive transfusion strategy. Subjects were 50 years and older, with cardiovascular disease and/or risk factors and hemoglobin <100 g/L within 3 days post-surgery. The average age was 82 years and 1527(76%) subjects were females. Intervention Demographics, health status and health services data were collected up to 60 days post-surgery and mortality to a median of 3 years post-surgery. Main outcomes Mortality, inability to walk and return home. Results US subjects had higher adjusted mortality than Canadians at 30 days (odds ratio = 1.78; 95% confidence interval: 1.09–2.90), 60 days (1.53; 1.02–2.29) and up to 3 years (hazard ratio = 1.25; 1.07–1.45). There were no differences in adjusted outcomes for walking ability or return home at 30 or 60 days post-surgery. Median hospital length of stay was longer (P < 0.0001) in Canada (9 days; interquartile range: 5–18 days) than the US (3 days; 2–5 days). US subjects (52.9%) were more likely than Canadians (16.8%) to be discharged to nursing homes for rehabilitation (P < 0.001). Conclusions Adjusted survival favored Canadians post hip fracture while walking ability and return home were not different between countries. The reason(s) for mortality differences warrant further investigation.